3D is not enough: Building up a cell instructive microenvironment for tumoral stroma microtissues. (1st January 2017) - Brancato, Virginia; Garziano, Alessandro; Gioiella, Filomena; Urciuolo, Francesco; Imparato, Giorgia; Panzetta, Valeria; Fusco, Sabato; Netti, Paolo A.
Graphical abstract: Abstract: We fabricated three-dimensional microtissues with the aim to replicate in vitro the composition and the functionalities of the tumor microenvironment. By arranging either normal fibroblasts (NF) or cancer-activated fibroblasts (CAF) in two different three dimensional (3D) configurations, two kinds of micromodules were produced: spheroids and microtissues. Spheroids were obtained by means of the traditional cell aggregation technique resulting in a 3D model characterized by high cell density and low amount of extracellular proteins. The microtissues were obtained by culturing cells into porous gelatin microscaffolds. In this latter configuration, cells assembled an intricate network of collagen, fibronectin and hyaluronic acid. We investigated the biophysical properties of both 3D models in terms of cell growth, metabolic activity, texture and composition of the extracellular matrix ( via histological analysis and multiphoton imaging) and cell mechanical properties ( via Particle Tracking Microrheology). In the spheroid models such biophysical properties remained unchanged regardless to the cell type used. In contrast, normal-microtissues and cancer-activated-microtissues displayed marked differences. CAF-microtissues possessed higher proliferation rate, superior contraction capability, different micro-rheological properties and an extracellular matrix richer in collagen fibronectin and hyaluronic acid. At last, multiphoton investigation revealed differences in the collagen network architecture. Taken together, these results suggested that despite to cell spheroids, microtissues better recapitulate the important differences existing in vivo between normal and cancer-activated stroma representing a more suitable system to mimic in vitro the stromal element of the tumor tissues. Statement of Significance: This work concerns the engineering of tumor tissue in vitro . Tumor models serve as biological equivalent to study pathologic progression and to screen or validate the drugs efficacy. Tumor tissue is composed by malignant cells surviving in a microenvironment, or stroma. Stroma plays a pivotal role in cancer progression. Current in vitro models, i.e. spheroids, can't replicate the phenomena related to the tumor stroma remodeling. For this reason, to better replicate the tumor physiology in vitro that include functional and morphological changes, a novel 3D cancer model is proposed.